Distant speech recognition - Wolfel, Matthias; McDonough, John (John W.). (Chichester, West Sussex, United Kingdom John Wiley & Sons, 2009)
A complete overview of distant automatic speech recognition. The performance of conventional Automatic Speech Recognition (ASR) systems degrades dramatically as soon as the microphone is moved away from the mouth of the speaker. This is due to a broad variety of effects such as background noise, overlapping speech from other speakers, and reverberation. While traditional ASR systems underperform for speech captured with far-field sensors, there are a number of novel techniques within the recognition system as well as techniques developed in other areas of signal processing that can mitigate th.
Acoustics -- Signal processing and filtering techniques -- Bayesian filter -- Speech feature extraction -- Speech feature enhancement -- Search : finding the best word hypothesis -- Hidden Markov model parameter estimation -- Feature and model transformation -- Speaker localization and tracking -- Digital filter banks -- Blind source separation -- Beamforming -- Hands on.
Includes bibliographical references and index.
Keywords: Automatic speech recognition